The Use of Solar Energy in Human Activities Throughout the Centuries - Silvi, Cesare (Annals of Arid Zone, 2016)
Renewable solar energy, in its direct and indirect forms (wind, hydro, forests and other biomass), has been the only powering source of energy of all human civilizations until 200 years ago. This paper, after a brief overview of sun’s energy use before the discovery and the fast-growing diffusion of coal, oil and natural gas, presents stories of the work of Italian scientists and engineers of the 19th and 20th centuries in exploring the possibility of producing steam by concentrating solar heat instead of obtaining it from burning fossil fuels, of which Italy is poor. Most of these accounts are little known, yet this Italian pioneering work continues to contribute today to the development of innovative concentrating solar - - thermal power plants with flat mirrors around the world. Key words: Solar energy, solar energy history, Italian solar energy pioneers, solar heat, concentrating solar thermal power, flat mirrors.